THE CONCEPT AND ESSENCE OF THE CATEGORY "DECENTRALIZATION": BASIC ASPECTS AND PROBLEMS OF MODERN UNDERSTANDING - VILGIN, Yevhen; TEDEEVA, Oleksandra (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This work summarizes the main scientific approaches to defining the category of decentralization and analyzes what decentralization is, its goals and objectives. In recent years, Ukraine has implemented a number of reforms, including the reform of state institutions, and therefore decentralization has been identified as one of the key priorities of the state policy of Ukraine, aimed at meeting public needs and improving the standard of living of the population. The concept of "decentralization", which is generally interpreted as the transfer of powers from state authorities to local self-government bodies, is characterized. In foreign countries, decentralization is interpreted as a kind of process of transfer of powers from state authorities to lower levels of management. The main types of decentralization are analyzed and defined: political, administrative, and fiscal, and the forms of decentralization are presented: devolution, delegation, and deconcentration. The article examines various scientific approaches to the definition of the concept of decentralization of state power and presents the author’s generalized definition of this category, which is based on the generalization of the views of economists. The results of the study show that the subjects of decentralization are state authorities and local self-government bodies. It has been proven that local self-government bodies can act as subjects of decentralization of public power, but not as subjects of decentralization of state power. The purpose of the decentralization of state power is the democratization of management, the main task of which is the demarcation of spheres of activity, functions and responsibilities between different levels of power and providing regions with an appropriate resource base. The main principles of decentralization of state power are highlighted: the principles of unity and systematicity, subsidiarity, subsidiarity, democracy and resource provision.